PROSPECTS OF DETERMINING SPIRITUAL-MORAL LIFESTYLE OF YOUNG FAMILIES - Inoyatova Saodatkhan Jahangir's daughter (American Journals Publishing, 2023)
This article reveals that the institution of the family as the primary social unit and its spiritual height depends on the healthy moral life. Functional and social differentiation of young families is determined by their spiritual and moral way of life.